Energy Efficiency and Time Management through IoT-Based Automated Electrical Control System and Digital Prayer Schedule Integration - Syaputra, Muhammad Adie; Sutomo, Budi; Saprudin, Usep; Putra, Muhammad Aqida (Politeknik Negeri Batam, 2025)
This study aims to develop an Internet of Things (IoT)-based automated electrical control system integrated with a digital prayer schedule to enhance energy efficiency and time management in mosques. Using IoT devices, electronic equipment such as air conditioners, lights, and loudspeakers can be automatically controlled according to prayer times, reducing energy waste and minimizing fire risks due to negligence in operating electrical devices. The study employs a prototyping method, where a system prototype is tested to evaluate its performance and effectiveness. A machine-to-machine bridge communication model is implemented to integrate the digital prayer schedule with mosque electrical devices. The research results are expected to provide an environmentally friendly technological solution while improving mosque operational efficiency. However, technical challenges, such as integrating the system with older electrical infrastructure, limited internet connectivity, and user readiness to operate new technology, must be addressed. Thus, this study contributes not only to energy efficiency but also to improving mosque management quality through digital technology.